Adolescent Alcohol Exposure Alters GABAA Receptor Subunit Expression in Adult Hippocampus. (November 2014) - Centanni, Samuel W.; Teppen, Tara; Risher, Mary‐Louise; Fleming, Rebekah L.; Moss, Julia L.; Acheson, Shawn K.; Mulholland, Patrick J.; Pandey, Subhash C.; Chandler, L. Judson; Swartzwelder, H. S.
<x xml:space="preserve">Abstract</x> Background The long‐term consequences of adolescent alcohol abuse that persist into adulthood are poorly understood and have not been widely investigated. We have shown that intermittent exposure to alcohol during adolescence decreased the amplitude of GABAA receptor (GABAAR)‐mediated tonic currents in hippocampal dentate granule cells in adulthood. The aim of this study was to investigate the enduring effects of chronic intermittent alcohol exposure during adolescence or adulthood on the expression of hippocampal GABAARs. Methods We used a previously characterized tissue fractionation method to isolate detergent resistant membranes and soluble fractions, followed by Western blots to measure GABAAR protein expression. We also measured mRNA levels of GABAAR subunits using quantitative real‐time polymerase chain reaction. Results Although the protein levels of α1‐, α4‐, and δ‐GABAAR subunits remained stable between postnatal day (PD) 30 (early adolescence) and PD71 (adulthood), the α5‐GABAAR subunit was reduced across that period. In rats that were subjected to adolescent intermittent ethanol (AIE) exposure between PD30 and PD46, there was a significant reduction in the protein levels of the δ‐GABAAR, in the absence of any changes in mRNA levels, at 48 hours and 26 days after the last ethanol (EtOH) exposure. Protein levels of the α4‐GABAAR subunit were significantly reduced, but mRNA levels were increased, 26 days (but not 48 hours) after the last AIE exposure. Protein levels of α5‐GABAAR were not changed by AIE, but mRNA levels were reduced at 48 hours but normalized 26 days after AIE. In contrast to the effects of AIE, chronic intermittent ethanol (CIE) exposure during adulthood had no effect on expression of any of the GABAAR subunits examined. Conclusions AIE produced both short‐ and long‐term alterations of GABAAR subunits mRNA and protein expression in the hippocampus, whereas CIE produced no long‐lasting effects on those measures. The observed reduction of protein levels of the δ‐GABAAR, specifically, is consistent with previously reported altered hippocampal GABAAR‐mediated electrophysiological responses after AIE. The absence of effects of CIE underscores the emerging view of adolescence as a time of distinctive vulnerability to the enduring effects of repeated EtOH exposure.